"Deveiling" Body Stories: Muslim Girls Negotiate Visual, Spatial, and Ethical "Hijabs" - Hamzeh, Manal (Race, Ethnicity and Education, 2011)
This article describes a collaborative research project that took place in two south‐western US border towns and sought to understand how four muslim Footnote 1 girls (age 14–17) expressed and negotiated their bodily learning experiences. Drawing on both the work of arab–muslim critical feminist Fatima Mernissi who utilized classical Islamic tools of research and my positionalities as arabyyah‐muslimah, I used insider’s methods to discuss how three hijabs (veils) – the visual, spatial, and ethical – acted as a central genderizing discourse that challenged the girls’ learning opportunities. This article shows how the girls’ parents enforced these three hijabs; how the girls questioned and deveiled the hijabs in their dress, mobility in public places, and physical behavior around boys. This inquiry is a call for critical feminist researchers and educators to recognize how these three hijabs form a key genderizing discourse in the lives of muslim girls. It also presents the importance of: (1) working with muslim girls as agents in their own lives; (2) critical engagement with difference between researchers/educators and muslim communities; and (3) practicing a critically reflexive pedagogy of deveiling.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; corps; cours; discipline; féminisme islamique; point de vue situé; premier cycle; pédagogie; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sex2283; sexualité; sociologie; thématiques; états-unis; états-unis (sud)

Les monologues voilés - Roosen, Adelheid; Germain, Greg; Drissi, Jamila (Axe sud, 2010)
Véritable blockbuster, Les Monologues Voilés ont rencontré un succès phénoménal dès la création au Théâtre de Poche de Bruxelles. Depuis, le spectacle a été joué plus de 180 fois - à guichets fermés - en Belgique et à Paris.Le spectacle nous propose 12 monologues d'une exceptionnelle intensité, drôles, poétiques, émouvants nous offrant le rare privilège d'entrer dans l'intimité de femmes musulmanes, sans fausse pudibonderie ni voyeurisme. [source jaquette].
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; afrique; approches et analyses; arabie saoudite; arts; asie; corps; cours; discipline; europe; féminisme islamique; irak; maroc; militance; pakistan; pays-bas; premier cycle; pédagogie; périodes historiques; régions géographiques; sex2283; somalie; thématiques; théâtre; turquie; égypte